Reactions of 'GaI' with organometallic transition metal halides - Coombs, N; Stasch, A; Aldridge, S (2008)
Two approaches towards the synthesis of phosphine ligated half-sandwich complexes [(ηx-CxHx)M(PR3)2GaI2]n containing diiodogallyl ligands have been investigated. Insertion of 'GaI' into the Mo-I bond of (η7-C7H7)Mo(CO)2I has been shown to yield the crystallographically characterized dimeric complex [(η7-C7H7)Mo(CO)2GaI2]2 (2). Attempts to substitute the carbonyl ligands by the phosphine ligand dppe [dppe = bis(diphenylphosphino)ethane] have been shown instead to yield the sparingly soluble complex [(η7-C7H7)Mo(CO)2GaI2]2(μ-dppe) (3) in which the phosphine bridges two [(η7-C7H7)Mo(CO)2GaI2] units via a pair of P → Ga donor/acceptor bonds. By contrast, attempts to insert 'GaI' directly into the metal-halogen bond of phosphine ligated complexes such as (η5-C5H5)Ru(PPh3)2Cl or (η5-C5H5)Ru(dppe)Cl have been shown to result in the formation of the tetraiodogallate species(η5-C5H5)Ru(PPh3)2(μ-I)GaI3 (5) and [(η5-C5H5)Ru(dppe)]+[GaI4]- (7). © 2007 Elsevier B.V. All rights reserved.